1998
DOI: 10.1143/jjap.37.4620
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Sensitivity and Stability of Fiber-optic Oxygen Sensor Using Several Cladding Polymers

Abstract: An attempt has been made to improve the sensitivity and stability of the polymer optical fiber (POF) sensor for continuous monitoring of gaseous oxygen. It utilizes the quenching phenomenon of cladding fluorescence. Three polymers namely, poly(cyclohexyl methacrylate) (PCMA), poly(l-menthyl methacrylate) (PMtMA) and poly(4-methyl-1-pentene), which have a relatively large oxygen permeability, were used as cladding layer doped with a sensitive dye such as a 9,10-diphenyl anthracene (DPA), on the polymer cores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The 1990s and 2000s saw a few contributions to the field of POF oxygen sensing. Notably by Morisawa et al [4], Toba et al [5], Chu and Lo [6] and Chu et al [7]. Of these, only Morisawa et al used a polymer matrix coated onto the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The 1990s and 2000s saw a few contributions to the field of POF oxygen sensing. Notably by Morisawa et al [4], Toba et al [5], Chu and Lo [6] and Chu et al [7]. Of these, only Morisawa et al used a polymer matrix coated onto the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the overall signal to noise (S/N) ratio of the detectable luminescent light, several reported studies have focused on using large-diameter, polymer type optical fibres (e.g. PMMA) for oxygen sensing [18] , [19] , which due to their larger surface area, provide improved S/N performance and are also suitable for invasive medical applications due to their inherent robustness when compared with standard silica fibres. Tapered-tip polymer fibre based oxygen sensors have also been investigated [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Fiber optic gas sensors (FOGS) have many advantages such as high accuracy, immunity from the disturbance of electric and magnetic fields, long life time, low cost and they have been studied all over the world. One kind of FOGS is the fluorescence quenching-based oxygen sensor(FQOS) which can be widely used in many fields and more and more studies on FQOS have been reported [1][2][3].One of the key procedures of developing high-performance FQOS is the immobilization of indicators. Sol-gel method is one of the common immobilization methods.…”
Section: Introductionmentioning
confidence: 99%